Slovenski podjetniški observatorij 2004. Del 2 - Rebernik, Miroslav; Tominc, Polona; Duh, Mojca; Krošlin, Tadej; Radonjič, Gregor (2005)
Slovenian Entrepreneurship Observatory 2004. Part 2. Slovenian Entrepreneurship Observatory was established in 1998 following the example of Observatory of European SMEs. With the Slovenian Entrepreneurship Observatory the Institute for Entrepreneurship and Small Business Management each year present a review of Slovenian SME demographics and in-depth research of current topics in the field of entrepreneurship. These results serve as the basis for proposals to provide government policy measures in different areas. The analysis of Slovenian enterprises in 2003 compared with the Europe was published in monograph Slovenian Entrepreneurship Observatory 2004, 1.part. In this issue, published as part of the series Slovenian Entrepreneurship Observatory, five authors discuss important aspects of the entrepreneurship. We report on research from the field of entrepreneurial growth aspirations, family businesses, innovation potential and challenges of its development and environmental certification and technological modernization of Slovenian manufacturing enterprises.
Keywords: empirična raziskava; aspiracije po rasti; družinsko podjetništvo; inovacijski potencial; okoljsko certificiranje; Empirical Analysis; Growth Aspirations; Family Business; Innovation Potential; Environmental Certification